Botanical Medicine for Women's Health - Aviva Romm; Mary L. Hardy; Simon Mills (Elsevier, 2010)
Use herbal medicines to treat women at any stage of life! Botanical Medicine for Women’s Health, 2nd Edition provides an evidence-based, patient-centered approach to botanical interventions for many different medical conditions. More than 150 natural products are covered, showing their benefits in gynecologic health, fertility and childbearing, and menopausal health. This edition includes new full-color photos of herbal plants along with a discussion of the role of botanicals in healthy aging. Written by Aviva Romm, an experienced herbalist, midwife, and physician, this unique guide is an essential resource for everyday practice of herbal medicine.
Keywords: Medicine; Gender (Identity); Género (Identidad)